Building Coalitions: Tapping Private Sector Resources - Elizabeth B. Bolton; Lisa Guion (EDIS)
This document is FY505, Part 13 of the 16 part series adapted for use in Florida by Elizabeth B. Bolton and Lisa Guion. Reprinted with permission March, 1997. Revised April, 2002.